Preparation and characterization of methylammonium tin iodide layers as photovoltaic absorbers (Phys. Status Solidi A 4∕2016). Issue 4 (April 2016) - Weiss, Manuel; Horn, Jonas; Richter, Christoph; Schlettwein, Derck
Abstract : Perovskite solar cells which are based on a hybrid organic‐ inorganic absorber material in the perovskite crystal structure have been of high interest recently. In just a few years the efficiency of these cells has surpassed dye‐sensitized solar cells, organic solar cells and amorphous silicon solar cells and achieved over 20%. The commonly used absorber material in these cells is CH3 NH3 PbX3 (X = I, Cl, Br). The inclusion of toxic lead represents a major problem, however, which might hinder the possible commercialization of perovskite solar cells in the future. Tin is supposed to be a promising replacement which is not examined well though, possibly because of the poor stability of the corresponding perovskite. The Editor's Choice article by Manuel Weiss et al. (pp.975–981 ) shows a two‐step preparation process for CH3 NH3 SnI3 where complete surface coverage is reached due to vapour‐deposition of SnI2 and subsequent conversion to the perovskite by spin‐coating using a solution of methylammonium iodide (CH3 NH3 I). X‐ray diffraction and UV‐Vis spectroscopy were used to demonstrate high stability, even in contact to air and under illumination.